VETERANS IN THE CIVIL SERVICE OF UKRAINE: INSTITUTIONAL CHALLENGES AND PROSPECTS FOR HR POLICY DEVELOPMENT - Zhylinska, Oksana; Dumnych, Ruslan (Public Management and Policy, 2026)
The article provides a comprehensive analysis of institutional challenges and development prospects of human resource policy aimed at integrating veterans into Ukraine’s civil service. In the context of a prolonged war and anticipated post-war recovery, the inclusion of veterans in public administration is considered a strategic resource for strengthening institutional capacity, enhancing public trust, and ensuring fair reintegration of defenders into civilian life. At the same time, the realization of this potential is constrained by systemic legal, organizational, and socio-psychological barriers that limit veterans’ access to public service positions. The empirical basis of the study relies on analytical reports of the Ukrainian Veterans Fund regarding employment barriers and adaptation needs of veterans, as well as academic publications in public administration and human resource management. The normative framework is grounded in current Ukrainian legislation on civil service, employment, and veteran policy, alongside relevant government regulations and strategic documents. A comparative analysis of veteran employment models in Poland and the United States is also conducted. Based on a SWOT analysis, the study identifies the strengths and weaknesses of the Ukrainian model, as well as opportunities for development and potential risks. Key directions for improving HR policy include the institutional recognition of military experience in terms of civilian competencies, the implementation of veteran-oriented recruitment procedures, the development of workplace adaptation standards, and the strengthening of digital tools and evidence-based data management. The findings emphasize the importance of balancing meritocratic principles with targeted support mechanisms for veterans, ensuring effective integration without compromising equal access to civil service.